RELIABILITY OF DIFFERENT METHODS OF DIAGNOSING INTESTINAL PARASITES IN HORSES - Oliveira de Macedo, Lucia; Antônio Bezerra Santos, Marcos; Câmara Alves, Leucio; Antonio Nascimento Ramos, Rafael; Aparecida de Carvalho, Gilcia (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Parasitism by intestinal nematodes may cause serious injuries to equines affecting their performance, given that the parasites compete for food and cause irritation, internal bleeding and anaemia. The diagnostic methods currently available are not efficient in detecting all the species of parasites simultaneously, hampering reliable diagnosis. Therefore, the purpose of this study was to evaluate four diagnostic methods for detecting equine intestinal parasites in the southern hinterland of Pernambuco, Brazil. Fecal samples (n = 87) were collected and examined through flotation based methods (Willis-Mollay, modified centrifugal flotation and EPG/OPG) and sedimentation (Hoffman). Of the total number of samples examined, 77.0% (67/87) were positive by modified centrifugal flotation; 44.8% (39/87) were positive by the Willis-Mollay method; 34.5% (30/87) by the Hoffman method and 28.7% (25/87) by the EPG/ OPG method. The Kappa index indicated moderate concordance between the Willis-Mollay and modified centrifugal flotation techniques (K= 0.477); Willis-Mollay and EPG/OPG (K=0.466); EPG/OPG and Hoffman (K= 0.425). In conclusion, modified centrifugal flotation presented high sensitivity for detection of parasites of the Strongylida order and Parascaris spp. It may, therefore, be used in association with the Willis-Mollay technique as a safe and accurate method of diagnosis